Սփիւռքահայ գրականութեան սահմանումին, անոր ձեւին եւ բովանդակութեան արդիականութեան, ձգտումներուն, ուղղութիւններուն, մարտահրաւէրներուն, այսօրուան լեզուին մասին հարցեր - Քասունի, Երուանդ հ., 1937- [հիմնադիր խմբագիր՝ 1970-1984]; Կռանեան, Անդրանիկ ծ. վրդ., 1929-2017 [1991-2017]; Տագէսեան, Անդրանիկ, 1960- [2018-] (տպ. Atlas)
In an attempt to better formulate the field of Armenian Diaspora literature and related issues three Armenian literary figures (Dr. Tamar Boyadjian, Dr. Karen Jallatian, Arkmenik Nikoghosyan) were asked to answer the following questions: a) Can you give a clear and concrete definition of Armenian Diaspora literature? If yes, then what is it; if no, then why? b) How modern is the current Armenian Diaspora Literature in its form and content? What are its objectrives (intentions )? c) What challenges does Armenian Diaspora Literature face? What are its developing tracks? d) How do you specify the current language of Armenian Diaspora literature? Alongside these literary figures the questions were emailed to artificial intelligence in August 2025. This paper is a compilation of their answers. This is the fourth series of questions being published in every second book of the Haigazian Armenological Review. The questions of the previous years revolved around issues related to Eastern and Western Armenian language, issues related to Armenian Studies, as well as issues related to Armenian historiography.
Keywords: Սփիւռքահայ գրականութիւն